Penilaian Kinerja Irigasi berdasarkan Pendekatan Permen PU no.32/2007 dan Metode Masscote dengan Evaluasi Rapid Appraisal Procedure (RAP) di Daerah Irigasi Barugbug - Jawa Barat - - Mulyadi; Indratmo Soekarno; Suardi Natasaputra (Jurnal Irigasi, 2014)
Irrigation performance is an indicator to description irrigation system management, Assesment Performance based on Permen PU 32/2007 made to the 6 (six) parameters including; Physical Infrastructure, Plant Productivity, Supporting Facilities, Personnel Organization, Documentation and Water User Association (P3A), whereas the assessment is carried out by evaluation method of MASSCOTE with Rapid Appraisal Procedure (RAP) which is a set of systematic procedures to diagnose obstacles, performance and level services in the system irrigation to 4 (four) main indicators include; Service Indicator, P3A Indicator, Human Resource of Operator Indicator, and Channel Operations Modernization indicator, performance assessment are taken by surveyor of respondents Operator irrigation, and farmers P3A, Show performance index by Permen PU 32/2007 gave the value 74.24% which has Well Performance Operations and Maintenance of Barugbug Irrigation, while the MASSCOTE methode show Performance 2.7 in level of Service which has Less Well Performance of Service and Operations Irrigation Channels. Based on the path analysis found significant influence with 4 (four) main indicator variables X1, X2, X3 and X4 to irrigation system performance variable (Y) of 0,701 or 70.1% with a residual error of 0.299 or 29.9%.